Implementation Of Ifrs 13 Fair Value Measurement: Issues And Challenges Faced By The Islamic Financial Institutions In Malaysia - Nathasa Mazna Ramli; Ainulashikin Marzuki; Abdul Rahim Abdul Rahman; Marziana Madah Marzuki (Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus/MyCite